Creating A Sustainable Development Model for the Trading of Industrial Minerals - FOUNTIS, ANASTASIOS; ARUNACHALAM, VIVEK (The journal of contemporary issues in business and government, 2021)
The research focuses on the Sustainable Development Goal 12 of the United Nations Millennium Development Program of responsible consumption and production of industrial minerals. The research creates an unique model called as the Centripetal Model using the Delphi Technique as well as other factors such as the macroeconomic concepts, cost analysis, market analysis (fragmentation and concentration) to justify the need for a Sustainable Development Framework. The Sustainable Development Model is necessary in the trading of industrial minerals since it raises the issues relating to the environmental issues and the researchers develop the centripetal model which helps in contributing the sustainable development of industrial minerals. This centripetal framework helps in responsible consumption of the industrial minerals, cement, aggregates and other natural resources which would contribute to responsible utilisation of the resources, develop the societal needs and improvise the conditions of all the different stakeholders associating with the minerals industry.